An output capacitor‐less low‐dropout regulator with wide load capacitance and current ranges. (16th January 2021) - Zhang, Zhang; Xu, Shu; Wu, Hongyuan; Xie, Guangjun; Cheng, Xin
Summary: This paper presents an output capacitor‐less low‐dropout regulator (LDO) with wide load capacitance and current ranges. A new Miller compensation technique called multipath double‐nested Miller compensation with Q‐reduction circuit is introduced to extend the ranges of the load capacitance and current. Besides, a multiple small‐gain stages technology is applied to improve the loop gain of the LDO, achieving better management accuracy. The proposed LDO was fabricated in a 130‐nm CMOS process. The measured maximum load capacitance can be extended to 4.7 nF, and the maximum load current is 80 mA. Moreover, the measured line regulation and load regulation are 4 mV/V and 0.154 mV/mA, respectively. Abstract : This paper presents an output capacitor‐less low‐dropout regulator with wide load capacitance and current ranges. A new Miller compensation technique called multipath double‐nested Miller compensation with Q‐reduction circuit is introduced to extend the ranges of the load capacitance and current, and a multiple small‐gain stages technology is applied to achieve better management accuracy. The measured maximum load capacitance and current are 4.7 nF and 80 mA, and the measured line regulation and load regulation are 4 mV/V and 0.154 mV/mA, respectively.